Senescent T Cell Induces Brown Adipose Tissue “Whitening” Via Secreting IFN-γ - Pan, Xiao-Xi; Yao, Kang-Li; Yang, Yong-Feng; Ge, Qian; Zhang, Run; Gao, Ping-Jin; Ruan, Cheng-Chao; Wu, Fang (Frontiers in Cell and Developmental Biology, 2021)
Aging-associated chronic inflammation is a key contributing factor to a cluster of chronic metabolic disorders, such as cardiovascular disease, obesity and type 2 diabetes. Immune cells particularly T cells accumulate in adipose tissue with advancing age, and there exists a cross talk between T cell and preadipocyte, contributing to age-related adipose tissue remodeling. Here, we compared the difference in morphology and function of adipose tissue between young (3-month-old) and old (18-month-old) mice and showed the phenomenon of brown adipose tissue “whitening” in old mice. Flow cytometry analysis suggested an increased proportion of T cells in brown adipose tissue of old mice comparing to the young, and exhibited senescent characteristics. We take advantage of co-culture system to demonstrate directly that senescent T cells inhibited brown adipocyte differentiation of preadipocytes in adipose tissue. Mechanistically, both in vitro and in vivo studies suggested that senescent T cells produced and released a higher level of IFN-γ, which plays a critical role in inhibition of preadipocyte-to-brown adipocyte differentiation. Taken together, the data indicate that senescent T cell-derived IFN-γ is a key regulator in brown adipocyte differentiation.